L’appropriation culturelle dans le secteur de la mode - Clara Gavelli (In Situ)
The copying of traditional designs by firms of the global fashion industry is a frequent occurrence, that is often denounced through the notion of cultural appropriation. Legally speaking, this phenomenon raises the issue of recognizing an ownership relation between traditional cultural expressions and the communities that perpetuate them. If traditional clothing designs and patterns are part of the “intangible cultural heritage”, the legal link with their cultural communities remains artificial. To overcome the inadequacy of this legal status, copyright appears at first sight to be a relevant means of regulating cultural exchanges, due to its patrimonial and moral dual nature. But collective cultural property is hard to conceive of in our legal system. The difficulties of extending this model to this type of creation, as well as the economic and cultural stakes underlying the notion of cultural appropriation, invite us to reconsider not only our symbolic representations, but also our legal relationships with things that surround us.